Influence of sintering temperature on density, hardness, shrinkage and microstructure of alumina-zirconia cutting tool - A. A., Anis; A. B., Hadzley; A. A., Umar; T., Norfauzi; Fairuz, M. R.; Herawan, S. G.; Thongkaew, Thongkaew (Universiti Malaysia Perlis (UniMAP), 2021)
The confederation of Alumina (Al2O3) and Zirconia (ZrO2) has emerged as a promising ceramic framework for advanced machine tool applications. The mechanical properties of the Al2O3-ZrO2 cutting tool are critically dependent on its density, hardness, and shrinkage, which are influenced by the powder preparation and sintering processes. The ef ect of sintering temperature on density, hardness, shrinkage, and microstructure of Al2O3-ZrO2 is investigated in this study. Al2O3 powders (80% wt) and ZrO2 powders (20% wt) were combined in a ball mill machine with polyethylene glycol (PEG) added as a binder agent. The samples were compacted using the cold isostatic pressing method at 300 MPa pressure after being pressed using a hydraulic hand press machine at 10 tons pressure. The green compacts were sintered at temperatures ranging from 1500°C to 1700°C, with soaking times ranging from 4 to 6 hours. The results show that as the sintering temperature increased, the density and hardness decreased. When the sintering temperature was set to 1500°C and the soaking time was 6 hours, the maximum hardness and density were recorded at 1321.23HV. Whereas, lowest hardness was recorded at 688.4HV when the sintering temperature was set to 1700°C and the soaking time was 6 hours. The shrinkage increased significantly as the sintering temperature increased, reaching a maximum of 9.95 percent at 1700°C after 4 hours of soaking. Microstructure analysis reveals that grain size increased as sintering temperature increased, with the smallest grain size presented 2 µm at 1500°C and 6 hours